If f(x)=3x-4 and g(x)=x^2, how do you find the value of f(3)-g(2)?

1 Answer
Jan 5, 2017

See complete process below:

Explanation:

First, we can find the formula for the subtraction without substitution:

f(color(red)(x)) - g(color(blue)(x)) = (3color(red)(x) - 4) - color(blue)(x)^2

We can now substitute the values for the functions:

f(color(red)(3)) - g(color(blue)(2)) = ((3 xx color(red)(3)) - 4) - color(blue)(2)^2

We can now solve the equation:

f(color(red)(3)) - g(color(blue)(2)) = (9 - 4) - 4

f(color(red)(3)) - g(color(blue)(2)) = 5 - 4

f(color(red)(3)) - g(color(blue)(2)) = 1